Molecular and cell-based therapies for muscle degenerations: a road under construction - Berardi, Emanuele; Annibali, Daniela; Cassano, Marco; Crippa, Stefania; Sampaolesi, Maurilio (Frontiers in Physiology, 2014)
There are no specific treatments for muscular degeneration caused by muscular dystrophies and for muscle wasting caused by cachexia or sarcopenia. Corticosteroid medications for dystrophic patients only helps to control inflammatory process and slightly delay the progression of the disease. Walkers and wheel chairs are the only options to maintain patients’ independence and walking capabilities until respiratory muscles become weak and mechanical ventilation is mandatory. On the other hand myostatin inhibition, melanocortin-4 receptor antagonists, β-blockers, IL-6 antagonism, and synthetic ghrelin are promising treatments for cachectic animal models. Although in both cases muscular degeneration is relevant the translational therapeutic attempts to find a possible cure are well defined. Molecular treatments are common options to explore beneficial treatments for cachexia, and gene/cell therapies are mostly employed to induce the phenotypic improvement of dystrophic muscles. This review deals with the use of molecular administrations and gene/stem cell therapy to treat muscular degenerations. It reviews previous trials using cell delivery protocols in mice and patients starting with the use of donor myoblasts, outlining the likely causes for their poor results and briefly focusing on satellite cell studies that raise new hope. Then it proceeds to describe recently identified stem/progenitor cells in relationship to their ability to home within a dystrophic muscle and to differentiate into skeletal muscle cells. Different known features of various stem cells are compared in this perspective, and the few available examples of their use in animal models of muscular degeneration are reported. This review also provides an outline of the role of microRNAs to control myogenic commitment. Finally, based on our current knowledge and the rapid advance in stem cell biology a prediction of clinical translation for cell therapy protocols combined with molecular treatments is discu